PARA ALÉM DO RAIO-X: DA PERCEPÇÃO AO DIAGNÓSTICO SISTÊMICO DA SAÚDE NA CIDADE MÉDIA DE SANTA MARIA, RS, BRASIL (Terr@ Plural, 2019)
The concept of health involves wide territories and different aspects of the existence of everyone, although, from the technical point of view, it seems to be restricted to a few standardized indexes. In this paper, we discuss the organic health situation in the municipality of Santa Maria, RS, as an attempt to approximate the general concept and the current state, as well as addressing the grave issue of the perception of well-being, a key concept of any prognostic elaboration in the area.